A Method for Estimating Number and Mass of Islets Transplanted within a Membrane Device - Kazuhisa Suzuki; Susan Bonner-Weir; Jennifer Hollister; Gordon C. Weir (Cell Transplantation, 1996)
Immunobarrier devices may prevent the immune destruction of pancreatic islets transplanted into diabetic recipients, but there are concerns about the survival of islets within such devices. In this manuscript we described a method for estimating islet mass and number within a membrane device. Five hundred syngeneic mouse islets were placed in a membrane device, which was then transplanted into the epididymal space of streptozotocin diabetic mouse. After 14 days the device was removed from the recipient, fixed, and embedded in paraffin. Sections were made and then stained with hematoxylin. From a total of 58 sections, 12 sample sections were selected for analysis by computerized planimetry to determine area of the device chamber and the islet area for each of these sections. By making certain assumptions, it was possible to estimate the total volume of the device chamber, the number of islets contained within the chamber, and the mass of islet tissue. Two weeks after implantation of the chamber, into which approximately 500 microencapsulated islets were loaded, the blood glucose level of the recipient fell to 73 mg/dL. The volume of the device chamber, the total volume of islets in the device, and the total islet number within the device were 1.78 μL, 0.57 μL, and 277 islets, respectively. The detailed methodology, assumptions, and calculations for this approach are described in this manuscript. This new method makes it possible to determine islet mass within a membrane device by analyzing a relatively small number of selected sections. This approach should make it possible to carry out comprehensive studies on the fate of transplanted islets contained in such immunobarrier membrane devices.